PENGARUH LATIHAN BALL FEELING DENGAN LATIHAN KOORDINASI TERHADAP PENINGKATAN KEMAMPUAN DRIBBLING BOLA PADA SISWA EKSTRAKULIKULER FUTSAL DI SMP NEGERI 1 CISAAT - Virgie Friyandika Mudhofar; Chairul Umam Ramadhan; Faiz Faozi ($$8@@&&$%K, 2022)
This study aims to determine the effect of ball feeling exercises with coordination exercises on improving ball dribbling ability in futsal extracurricular students at SMP Negeri 1 Cisaat. This research is a study that uses experimental methods, with a one-group pretest-posttest design. The population in this study was futsal extracurricular students at SMP Negeri 1 Cisaat which amounted to 20 students. Sampling technique using purposive sampling method, treatment was carried out for 16 meetings. The instrument used for the ball dribbling ability test is the dribbling test instrument by (Rahma Dewi, Muhammad Takwa Pakpahan, 2018: 4, referred to in Rina Aryati, 2022: 49). The data analysis technique uses a t paired sample t test by comparing the pretest results with the posttest in the experimental group. The results of the hypothesis test obtained a value of t 18.886 and the significance value was 0.000. Because the sig value is 0.000 < 0.05, it can be concluded that the value is strongly correlated so that H0 is rejected and H1 is accepted, meaning that there is a significant influence on ball feeling exercises with coordination exercises on improving ball dribbling ability in futsal games in futsal extracurricular students at SMP Negeri 1 Cisaat. Percentage increase in ball dribbling ability with ball feeling exercises with coordination exercises (16.95 %).